Common occurrence of Enterocytozoon bieneusi genotypes SHR1 and PL2 in farmed masked palm civet (Paguma larvata) in China. (December 2021) - Lin, Xuhui; Xin, Luyao; Cao, Yangwenna; Hou, Minyu; Qiao, Fei; Li, Juan; Qi, Meng; Sun, Mingfei
Abstract: Enterocytozoon bieneusi is a common pathogen in a broad range of vertebrate hosts. To assess the prevalence and genotypes of E. bieneusi in farmed masked palm civet ( Paguma larvata ), 537 fecal samples from seven provinces in China were tested by nested PCR of the polymorphic internal transcribed spacer (ITS) region. Among of all the samples, 60.0% (325/531) were positive for E. bieneusi, with the highest prevalence in Hebei province (85.0%). Sequence analysis revealed the presence of nine E. bieneusi genotypes, including four known genotypes (SHR1, PL2, PL4, CHG19) and five novel genotypes (PL12 to PL16). Genotypes SHR1 and PL2 were the most common genotypes in seven provinces. Phylogenetic analysis showed that three genotypes (CHG19, PL4 and PL16) were distributed to Group 1, and six genotypes (SHR1, PL2, PL12, PL13, PL14 and PL15) formed a novel clade, which was named group 12. Findings highlight the need to conduct additional research to elucidate the epidemiology of E. bieneus i in farmed masked palm civet. Graphical abstract: Image 1 Highlights: ● The overall infection rate of Enterocytozoon bieneusi was 60.0% (325/537) in farmed masked palm civet ( Paguma larvata ) in China. ● Nine genotypes were identified, including four known genotypes (SHR1, PL2, PL4, CHG19) and five novel genotypes (named as PL12 to PL16). ● Genotypes in farmed masked palm civet formed a novel clade which was named as group 12.